Estriol serum levels in new and chronic users of vaginal estriol cream: A prospective observational study. Issue 4 (9th April 2020) - te West, Nevine I. D.; Day, Ric O.; Hiley, Basia; White, Chris; Wright, Mike; Moore, Kate H.
Abstract: Aims: To quantify estriol serum concentrations in "new" and "chronic users" of topical estriol cream using quantitative liquid chromatography tandem mass spectrometry. Methods: In this singlecentre prospective observational study, postmenopausal women with urogynaecological complaints were enrolled: 40 had not used topical estriol previously ("new users") and 50 had been applying estriol cream for more than 12 weeks ("chronic users"). In "new users, " serum estriol levels were measured at baseline and after 12 weeks use. Estriol cream 1 mg/g was used daily for 3 weeks, then twice weekly with applicator (group 1A) or digitally (group 1B) or three times per week digitally (group 1C). "Chronic users" applied the cream twice (n = 7) or three (n = 43) times per week. Serum samples were taken in the morning after using cream the previous night. The main outcome measures were estriol serum concentrations in "new" and "chronic users" of estriol cream. Results: Baseline serum estriol concentrations were less than 5 pmol/L in all 40 "new users." At 12 weeks, the 12‐hour serum estriol levels ranged from less than 5 to 494 pmol/L (median 22.8; Interquartile range [IQR] 9.2–108.5). Seven "new users" had levels more than 100 pmol/L. Most of the 50 "chronic users" also had 12‐hour levels less than 100 pmol/L (median 15.1 pmol/L [IQR 2.7–33.9]: three had levels more than 100 pmol/L. Conclusions: This study reports serum estriol concentrations in a large number of "new" and "chronic users" of vaginal estriol cream, employing a novel highly sensitive and specific technique. Overall, the results are reassuring: 87% had 12‐hour estriol levels less than 100 pmol/L.